2016
DOI: 10.1039/c6sc00889e
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic labelling of cholesteryl glucosides in Helicobacter pylori reveals how the uptake of human lipids enhances bacterial virulence

Abstract: Helicobacter pylori infects approximately half of the human population and is the main cause of various gastric diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 46 publications
3
44
0
Order By: Relevance
“…Upon uptake of cholesterol, H. pylori employs cholesterol glucosyltransferase (CGT) to convert cholesterol to CG, followed by the reaction of CGAT to catalyze the acyltransfer to produce CAG. We previously demonstrated that CAG, rather than CG or cholesteryl 6′-O-phosphatidyl-α-D-glucopyranoside, was able to promote lipid rafts clustering in the host cell membranes, as well as CagA translocation and phosphorylation 14 . Wang et al 13 reported that the loss of cholesteryl-α-glucoside derivatives abolished the adhesion of H. pylori to AGS cells 13 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Upon uptake of cholesterol, H. pylori employs cholesterol glucosyltransferase (CGT) to convert cholesterol to CG, followed by the reaction of CGAT to catalyze the acyltransfer to produce CAG. We previously demonstrated that CAG, rather than CG or cholesteryl 6′-O-phosphatidyl-α-D-glucopyranoside, was able to promote lipid rafts clustering in the host cell membranes, as well as CagA translocation and phosphorylation 14 . Wang et al 13 reported that the loss of cholesteryl-α-glucoside derivatives abolished the adhesion of H. pylori to AGS cells 13 .…”
Section: Resultsmentioning
confidence: 99%
“…Identification and characterization of H. pylori CGAT. Previously phospholipids were shown to serve as the precursors for the biosynthesis of CAG and cholesteryl 6′-O-phosphatidyl-α-Dglucopyranoside 14 . In an attempt of identifying the enzyme to catalyze the formation of CAGs, we performed several geneknockout strains related to phospholipase, esterase, or acyltransferase (see Methods section for the list of candidates) by inserting a kanamycin-resistance cassette into desirable genes of H. pylori 26695.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the enzyme proteins involved in the synthesis of either CAG or CPG remain to be clarified, a recent study by other group has demonstrated that the enzymatic activities for the synthesis of CAG and CPG are detected in H. pylori's o u t e r membrane and inner membrane, respectively [16]. In addition, both enzymatic activities for the synthesis of CAG and CPG turned out to use phosphatidylethanolamine (PE) as the substrate [16]. In sum, the CGL acyltransferase (CGLAT) transfers a fatty acid derived from PE to the CGL and thereby synthesizes CAG.…”
Section: Introductionmentioning
confidence: 99%